Plasma Cell Gingivitis: A Case Report - Arulraj, P.; Subramanian, P.; Paramasivam, Arun Kumar; M, Senthilkumaran; M, Navarasu; R, Dhivya (Journal of Neonatal Surgery, 2025)
Plasma cell gingivitis is a diagnostic predicament for all the clinicians. ‘’It is also referred to as atypical gingivostomatitis, idiopathic gingivostomatitis, allergic gingivostomatitis, and plasma cell gingivostomatitis’’ which are make more distinctive by bright red gingiva and easily bleeds on probing. It is frequently confused with inflammatory gingival enlargement, erythematosus lichen planus, and other lesions. One such rare and benign entity is discussed in this article and managed after thorough clinical, radiological, histopathological, immunohistochemistry examination